Hormones and mammary carcinogenesis in mice, rats, and humans: a unifying hypothesis. - Nandi, S (1995)
An attempt has been made to put forward a unifying hypothesis explaining the role hormones play in the genesis of mammary cancers of different phenotypes and genotypes in mice, rats, and humans. Most mammary cancers in these species originate in luminal mammary epithelial cells lining the mammary ducts and alveoli. These cancers are histopathologically diverse and are classified on the basis of growth requirements as hormone-dependent or hormone-independent tumors. In most strains of mice, mammary cancers at the time of detection are largely of the hormone-independent type; in rats, almost all mammary cancers are hormone-dependent, while humans have both phenotypes. In spite of these differences, in vivo studies show that hormones (ovarian and pituitary) are essential for luminal mammary epithelial cell proliferation and also for the development of mammary cancers of both hormone-independent and hormone-dependent types. This article, based on our extensive in vivo and in vivo studies and on current literature, proposes a model to explain the central role of hormones in the genesis of all types of mammary cancers. The model attempts to address the following questions: (i) how hormones regulate luminal mammary epithelial cell proliferation, (ii) why hormones are required for the genesis of mammary cancers of all phenotypes and genotypes, including those which are always classified as hormone-independent tumors, and (iii) why the three species (mouse, rat, and human) have consistently different ratios of hormone-dependent to hormone-independent tumors.